Welfare programs and labor supply in developing countries: Experimental evidence from Latin America - María Laura Alzúa; Guillermo Cruces; Laura Ripani (Institute for the Study of Labor (IZA), 2012)
This study looks at the effect of welfare programs on work incentives and the adult labor supply in developing countries. The analysis builds on the experimental evaluations of three programs implemented in rural areas: Mexico's PROGRESA, Nicaragua's RPS and Honduras' PRAF. Comparable results for the three countries indicate that the effects that the programs have had on the labor supply of participating adults have been mostly negative but are nonetheless small and not statistically significant. However, the evidence does point to the presence of other effects on labor markets. In the case of PROGRESA, there is a small positive effect on the number of hours worked by female beneficiaries and a sizeable increase in wages among male beneficiaries and a resulting increase in household labor income. Moreover, PROGRESA seems to have reduced female labor-force participation in ineligible households. These results imply that large-scale interventions may have broader equilibrium effects.
Keywords: J08; J22; I38; 330; welfare programs; income support; labor supply; work incentives; conditional cash transfers; randomized control trials; developing countries; Sozialhilfe; Arbeitsangebot; Entwicklungsländer; Lateinamerika